Dialogue in the interpretation of the other - Ponce-Bogino, Héctor (2008)
A way to interpret another person’s identity is to interact with her through different means. Whence decoding preverbal and paraverbal features of another person, as well as reading some of her writings or conversing with her, the interpreter interacts with an agent in three steps. First, the interpreter attributes her own beliefs to the agent; second, formulates new hypotheses to render the agent’s behavior more coherent; and third, expands her own beliefs attributed to the agent as a result of the interaction and sharing of their beliefs. In this paper, it will be shown that some of the assumptions of Modernity are imbedded in our interpretative practices and how we should overcome these assumptions. To this end, a contrast between the model of interpretation and the dialogue model will be drawn. Finally, an argument for the adoption of a extended ethnocentrism over universalism will be presented.